PENGARUH PERMAINAN TRADISIONAL GALASIN TERHADAP PENINGKATAN KEBUGARAN JASMANI SISWA KELAS IV SEKOLAH DASAR NEGERI SUKADAMI KECAMATAN MANGKUBUMI KOTA TASIKMALAYA - Nina Ujiana (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2023)
The main problem behind tis research is the low level of physical fitness of the fourth grade students of SDN Sukadami in Physical Education subjects. This research was conducted with the aim of knowing the level of physical fitness of students after being given treatment of the traditional game of galasin in the learning process. This study used a quasi-experimental method with a nonequivalent control group design. The population in this study were the fourth grade students of SDN Sukadami, amounting to 27 students. The sampling technique used is a saturated sample. In this study, data collection techniques were used by conducting the Indonesian Physical Fitness Test, in the form of pretest and posttest. Based on the results of data processing, data analysis, and hypothesis testing, it shows that there are differences in the results of the pretest and posttest obtained by students in the experimental group and the control group. The average pretest value obtained by the experimental group was 13.31 and the posttest value was 17.31, an increase of 4.00. Meanwhile, in the control group the average pretest score was 14.36 and the posttest score was 15.50, an increase of 1.14. Based on the data obtained, it was shown that the experimental group was superior to the control class. The results of the paired sample t-test with a significance level of 5% with the help of SPSS 25 obtained a sig (2-tailed) value of 0.000. This means that there is a significant difference in the results of the pretest and posttest of fourth grade students at SDN Sukadami in the experimental group who were treated with the traditional game of galasin.